Pemodelan Lingkungan Virtual untuk Interaksi Avatar Berbasis Context Pada Proyek Digital Life at Campus (DiL@C) - Sajati, Haruno; Nugroho, Lukito Edi; Ferdiana, Ridi (Universitas Atma Jaya Yogyakarta, 2012)
Abstract. Campus activities that use information technology increasing rapidly, these activities e.g. studying activity, access to information and so on. The increased activities forces instance has an